Quantitative Ubiquitinomics Revealed Abnormal Ubiquitinated ATP7A Involved in Down-Regulation of ACTH in Silent Corticotroph Adenomas - Zhao, Sida; He, Yue; Wang, Hongyun; Li, Dan; Gong, Lei; Zhang, Yazhuo; Li, Chuzhong (Frontiers in Endocrinology, 2022)
Ubiquitination is reported to be a critical biological event on ACTH secretion in corticotroph adenomas. However, the effect of ubiquitylation on ACTH secretion in silent corticotroph adenomas (SCAs) remains unclear. The aim of our study was to explore the mechanism of decreased secretion of ACTH in SCAs with ubiquitinomics. The differently expressed ubiquitinated proteins between SCAs and functioning corticotroph adenomas (FCAs) were identified by 4D lable-free mass spectrometer, followed by bioinformatics analysis. The function of the candidate ubiquitinated protein ATP7A (K333) was validated in AtT20 cells. A total of 111 ubiquitinated sites corresponding to 94 ubiquitinated proteins were typically different between SCAs and FCAs. Among all the ubiquitinated sites, 102 showed decreased ubiquitination in SCAs, which mapped to 85 ubiquitinated proteins. Pathway enrichment analysis revealed that ubiquitinated proteins were mainly enriched in vesicle pathway and protein secretion pathway. ATP7A (K333) was one of the proteins enriched in vesicle pathway and protein secretion pathway with decreased ubiquitination level in SCAs. In vitro assay indicated that both ATP7A siRNA and omeprazole (ATP7A protein inhibitor) increased the secretion of ACTH in AtT20 cell supernatant compared to control groups (p<0.05). These results indicated that ATP7A may be related to the abnormally expression of ACTH in SCAs and potential for the treatment of SCAs.